Jun Dimerization Protein 2 Controls Senescence and Differentiation via Regulating Histone Modification. (12th December 2010) - Huang, Yu-Chang; Hasegawa, Hitomi; Wang, Shin-Wei; Ku, Chia-Chen; Lin, Ying-Chu; Chiou, Shyh-Shin; Hou, Ming-Feng; Wu, Deng-Chyang; Tsai, Eing-Mei; Saito, Shigeo; Yamaguchi, Naoto; Yokoyama, Kazunari K.
Abstract : Transcription factor, Jun dimerization protein 2 (JDP2), binds directly to histones and DNAs and then inhibits the p300-mediated acetylation both of core histones and of reconstituted nucleosomes that contain JDP2 recognition DNA sequences. JDP2 plays a key role as a repressor of adipocyte differentiation by regulation of the expression of the gene C/EBPδ via inhibition of histone acetylation. Moreover, JDP2-deficient mouse embryonic fibroblasts (JDP2 −/− MEFs) are resistant to replicative senescence. JDP2 inhibits the recruitment of polycomb repressive complexes (PRC1 and PRC2) to the promoter of the gene encoding p16 Ink4a, resulting from the inhibition of methylation of lysine 27 of histone H3 (H3K27). Therefore, it seems that chromatin-remodeling factors, including the PRC complex controlled by JDP2, may be important players in the senescence program. The novel mechanisms that underline the action of JDP2 in inducing cellular senescence and suppressing adipocyte differentiation are reviewed.